Developmental trajectories of children's playfulness in two- to six-year-olds - Wustmann Seiler, Corina; Duss, Isabelle; Rüdisüli, Cornelia; Lannen, Patricia (Frontiers in Developmental Psychology, 2024)
Even though playfulness has been found to be highly relevant to the development and wellbeing of young children, hardly any longitudinal findings are available on stability and changes in children's playfulness. This study examined developmental trajectories of children's playfulness in two-to six-year-olds over a two-year period and analyzed whether individual and family characteristics and transition to primary school explain these trajectories. The sample included 839 children (47.3% girls, MAge = 4.87 years, SDAge = 1.39) from 38 childcare centers and 47 kindergartens in Switzerland. Children's playfulness was assessed at three measurement time points at one-year intervals using the multidimensional Children's Playfulness Scale to gather parent and teacher reports. Second-order linear growth curve models showed significant interindividual differences in children's playfulness at initial baseline. These differences correlated with effects for age, migrant background, and maternal education. The growth-related processes varied depending on children's age, and the individual dimension of children's playfulness whether an increase, stability, or decline was observed. In particular, social components of playfulness were found to change. On average, children's playfulness increased in early years but decreased from school age onwards. However, closeness in parent-child relationships proved to be supportive of children's playfulness at all time points. The results indicate the significance of positive parenting to children's playfulness, but they also draw attention to how playful qualities can be maintained and more highly valued in the school environment. In general, the study can contribute to a better understanding of the construct of playfulness in childhood.